2015
DOI: 10.1002/hep.27774
|View full text |Cite
|
Sign up to set email alerts
|

Increased duodenal iron absorption through up‐regulation of divalent metal transporter 1 from enhancement of iron regulatory protein 1 activity in patients with nonalcoholic steatohepatitis

Abstract: Increased hepatic iron accumulation is thought to be involved in the pathogenesis of nonalcoholic steatohepatitis (NASH). Hepatic iron accumulation, as well as oxidative DNA damage, is significantly increased in NASH livers. However, the precise mechanism of iron accumulation in the NASH liver remains unclear. In this study, 40 cases with a diagnosis of NASH (n 5 25) or simple steatosis (SS; n 5 15) by liver biopsy were enrolled. An oral iron absorption test (OIAT) was used, in which 100 mg of sodium ferrous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 41 publications
(79 reference statements)
1
54
0
Order By: Relevance
“…Estimates of liver iron concentration by MRI were in the middle of the normal range at 23 µmol/g. In the study of Hoki et al, mean serum ferritin was 182 µg/L, and of the 40 patients reported, there were only 2 of 40 (5%) with 3+ iron staining and none with 4+ staining. Therefore, it may not be surprising that iron reduction therapy had no obvious benefits given that the patients did not have iron overload.…”
supporting
confidence: 89%
“…Estimates of liver iron concentration by MRI were in the middle of the normal range at 23 µmol/g. In the study of Hoki et al, mean serum ferritin was 182 µg/L, and of the 40 patients reported, there were only 2 of 40 (5%) with 3+ iron staining and none with 4+ staining. Therefore, it may not be surprising that iron reduction therapy had no obvious benefits given that the patients did not have iron overload.…”
supporting
confidence: 89%
“…Similarly, it has recently been reported that increased iron absorption despite high hepcidin levels occurs in patients with nonalcoholic steatohepatitis possibly associated with mild iron overload, compared to that observed in patients with simple steatosis . This was associated with upregulation of duodenal iron absorption again via induction of Divalent Metal Transporter‐1 . Although our study was not designed and powered to test an impact of liver damage on iron metabolism, we did not detect any difference in iron absorption between patients with steatohepatitis and simple steatosis, suggesting that altered iron metabolism in DIOS is not a consequence of liver damage.…”
Section: Discussionmentioning
confidence: 38%
“…Similarly, it has recently been reported that increased iron absorption despite high hepcidin levels occurs in patients with nonalcoholic steatohepatitis possibly associated with mild iron overload, compared to that observed in patients with simple steatosis . This was associated with upregulation of duodenal iron absorption again via induction of Divalent Metal Transporter‐1 .…”
Section: Discussionmentioning
confidence: 82%
“…Hoki et al . [43] studied 40 subjects with a mean serum ferritin level of 182 μg/L. Only 5% had + 3 iron staining, and none had + 4 staining.…”
Section: Discussionmentioning
confidence: 99%